(untitled) (Construction Economics and Building, 2012)
The efficiency of any transport operation isdependent on the degree to which vehiclecapacity is utilised on the forward and returntrips. Efficiency requirements create thelogistical challenges of finding backloads forreturning vehicles. In the absence ofbackloads, vehicles travel empty on the returnjourney. Construction is fundamentallydifferent from other freight services in thatapart from requiring large quantities of materialinputs, it also generates appreciable levels ofwaste. There is therefore, potential forreducing empty running by construction trucksthrough back-loading waste to points ofdisposal, reuse, recycling or reclamation.Back-loading, which is one of the reverselogistics processes is important for returningproducts that are damaged, obsolete or wornout and those unacceptable to buyers. Backloadingis also associated with utilising sparecapacity in the supply chain to increase returnon truck investment. This paper examines theoperations and processes associated withconstruction materials and waste logistics andassesses the potential for reduction in truckempty running through utilisation of thereverse logistics concept.